TEKNIK MANAJEMEN STRES YANG EFEKTIF PADA REMAJA - Patricia Gunadhi, Leony; Salsabila, Najwa Raudhah; Rosalina, Sinta (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
Adolescent stress management techniques are techniques used to reduce or suppress stress levels in adolescents. The prevalence of stress among young people in the world has reached an alarming rate of about 5 to 70 percent. Stress management techniques aim to reduce the prevalence of stress in young people. Literature research and the use of Google Scholar in the last six years is one of the methods. The results were 17,000 journals with the keyword stress management in adolescents, the results were filtered into sixteen journals. The results showed that there are some effective stress management techniques for adolescents.